(untitled) (Research, Society and Development, 2022)
The present work aims to simulate a CO2 absorber using, from HPWS technology, water as solvent and bed-packed with Pall rings and analyze the influence of operational variables in the biogas refining plant. In the study, several values are tested, in the ASPEN PLUS® V8.8 software, for the flow of solvent fed, pressure, and temperature of the tower, to establish optimal values for these variables. The results obtained proved to be more effective for the purity of the treated biogas and the CO2 removal and presented a lower operating cost.